Differences in health and health inequalities between Australia and New Zealand - Imlach Gunasekara, F (My University, 2011)
There are vast differences in health and inequalities in health between different population groups and nations. We compared scores on the Short Form 36 Questionnaire (SF-36), a widely used measure of health-related quality of life, using data from wave 8 (2008) of the Household Income and Labour Dynamics in Australia (HILDA) Survey and wave 7 (2008/2009) of the Survey of Family Income and Employment (SoFIE), the equivalent New Zealand longitudinal survey. Overall, SoFIE respondents score significantly higher (i.e. better) on the mental and general health SF-36 domains than do HILDA respondents. This may be due to population differences or differences in the sample designs or administration of the questionnaires. Males in both surveys generally report better SF-36 scores than females but in SoFIE, both males and females have flat and/or improving SF-36 scores in all the mental health domains with increasing age, but declining with age for physical health scores. In HILDA, only the vitality and mental health domains showed increases with age (for men and women). To investigate differences in health inequalities we compared concentration indices examining the distribution of reported health across income in working age (20-65 year old) men and women. Income-related health inequalities were present in both samples, with better health in high income groups. Decomposition analyses, to identify the relative contribution of various health determinants to the inequality, found that age, income, area deprivation and being inactive in the labour force were major contributors to income-related health inequality, in both HILDA and SoFIE, and for both mental health and physical health measures.
Keywords: Health -- Physical; Health; Health -- Mental; Health and wellbeing; Health; Mental; Physical; Health and wellbeing